Metastatic immune infiltrates correlate with those of the primary tumour in canine osteosarcoma - Withers, Sita S.; York, Daniel; Choi, Jin W.; Woolard, Kevin D.; Laufer-Amorim, Renee [UNESP]; Sparger, Ellen E.; Burton, Jenna H.; McSorley, Stephen J.; Monjazeb, Arta M.; Murphy, William J.; Canter, Robert J.; Rebhun, Robert B. (Wiley, 2019)
Our lack of understanding of the immune microenvironment in canine osteosarcoma (cOSA) has limited the identification of potential immunotherapeutic targets. In particular, our ability to utilize readily available tissue from a dog's primary tumour to predict the type and extent of immune response in their pulmonary metastatic lesions is unknown. We, therefore, collected 21 matched pairs of primary tumours and pulmonary metastatic lesions from dogs with OSA and performed immunohistochemistry to quantify T-lymphocyte (CD3), FOXP3+ cell, B-lymphocyte (Pax-5), and CD204+ macrophage infiltration. We found that T-lymphocytes and FOXP3+ infiltrates in primary tumours positively correlated with that of metastatic lesions (ρ = 0.512, P = 0.038 and ρ = 0.698, P = 0.007, respectively), while a strong trend existed for CD204+ infiltrates (ρ = 0.404, P = 0.087). We also observed T- and B-lymphocytes, and CD204+ macrophages to be significantly higher in a dog's pulmonary metastasis compared to their primary tumour (P = 0.018, P = 0.018, P = 0.016, respectively), while FOXP3+ cells were only significantly higher in metastases when all primary tumour and metastasis lesions were compared without pairing (P = 0.036). Together, these findings suggest that the metastatic immune microenvironment may be influenced by that of the primary cOSA, and that primary tumour immune biomarkers could potentially be applied to predict immunotherapeutic responses in gross metastatic disease. We, therefore, provide a rationale for the treatment of cOSA pulmonary metastases with immunotherapeutics that enhance the anti-tumour activity of these immune cells, particularly in dogs with moderate to high immune cell infiltration in their primary tumours.
Keywords: dogs; immunotherapy; neoplasm metastasis; osteosarcoma; tumour microenvironment